Produk Tabungan Emas Pegadaian Syariah Sebagai Alternatif Investasi Halal - Irma Niawati; Andriani (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to examine the Pegadaian Syariah Gold Savings product as a halal investment alternative for Muslims in Indonesia. The background of this study is the increasing public interest in gold investment and the need for sharia-compliant financial instruments. Using a qualitative approach with descriptive methods, this study relies on secondary data from literature, journals, and official sources from Pegadaian Syariah. The study results indicate that Pegadaian Syariah Gold Savings offers various advantages such as guaranteed halal transactions, potential long-term profits, high accessibility, security and transparency, and protection against inflation. This product not only meets investment needs but also supports financial management in accordance with Islamic values. With a sale and purchase agreement (murabahah) and custody mechanism, as well as supervision by the DSN-MUI, Pegadaian Syariah Gold Savings is a halal, inclusive, and sustainable investment solution.